إثيقا المسؤولية عند هانس يوناس - عمراني, عبير; زوزو, سمر (جامعة الوادي - University of Eloued, 2023)
Abstract : The sense of responsibility according to Hans Jonas is represented in that responsibility that a person is supposed to bear in order to guarantee the rights of future generations, as this responsibility is characterized as a “future responsibility.” Fear is also the first motive and the first means to achieve this responsibility. In addition, this responsibility does not belong to Not only the human being, but our responsibility towards other living beings as well as the environment and its wealth. Where Hans Jonas considers our responsibility towards nature and the rest of the beings as a natural parental responsibility stemming from that spontaneous emotional sense towards these assets and towards future generations. The Jonas philosophy had a role in changing the views of many organizations and philosophies that coincided with it on the one hand, and the philosophies that came after it on the other hand. . Hans Jonas's commitment to responsibility also represented a call to all humanity. Which made scientists, thinkers, and even researchers take into account the ethics of responsibility in their research and work. Accordingly, it can be said that Hans Jonas has awakened humanity from its slumber that modern technologies have put in it. الملخص: إن اتيقا المسؤولية عند هانس يوناس تتمثل في تلك المسؤولية التي يفترض على الإنسان تحملها من أجل ضمان حقوق الأجيال القادمة ,حيث تتصف هذه المسؤولية "بالمسؤولية المستقبيلة".كما أن الخوف يمثل الدافع الأول والوسيلة الأولى لتحقيق هذه المسؤولية .بالإضافة إلى أن هذه المسؤولية لا تخص الكائن البشري فقط بل تشمل مسؤوليتنا تجاه الكائنات الحية الأخرى وكذا البيئة وثرواتها. حيث يعتبر هانس يوناس مسؤوليتنا تجاه الطبيعة وبقية الكائنات كالمسؤولية الأبوية الطبيعية النابعة من ذلك الحس الشعوري التلقائي نحو هذه الموجودات ونحو الأجيال القادمة.وقد كان للفلسفة اليوناسية دور في تغيير وجهات نظر العديد من المنظمات والفلسفات المزامنة له من جهة ,والفلسفات التي جاءت بعده من جهة أخرى . كما أن اتيقا المسؤولية لهانس يوناس مثلت دعوة لكل الإنسانية. مما جعل العلماء والمفكرين وحتى الباحثين يأخذون بعين الإعتبار أخلاقيات المسؤولية في بحوثهم وأعمالهم .وعليه يمكن القول أن هانس يوناس قد أيقض الإنسانية من سباتها الذي وضعته فيها التكنولوجيات الحديثة.
نمودجا
مذكرة ماستر فلسفة
Keywords: اتيقا, هانس يوناس, المسؤولية; Etika, Hans Jonas, Responsibility